Slow light mach-zehnder electro-optic modulator based on oxide-cladding aluminum nitride photonic crystal - Melo, Emerson G.; Carvalho, Daniel O. [UNESP]; Carreño, Marcelo N. P.; Alayo, Marco I. (Optica Publishing Group, 2016)
We study the effects of slow light in the performance parameters of a Mach-Zehnder electro-optic modulator based on oxide-cladding AlN photonic crystal. A sub-1V modulation voltage can be obtained for modulation lengths of few micrometers.